Reconstruction of instantaneous surface normal velocity of a vibrating structure using interpolated time-domain equivalent source method. (July 2018) - Geng, Lin; Bi, Chuan-Xing; Xie, Feng; Zhang, Xiao-Zheng
Highlights: The interpolated time-domain equivalent source method is extended to reconstruct the instantaneous surface normal velocity. The time-evolving particle velocity on the hologram surface is used as the input. The extended method is compared with the method based on pressure measurements. Abstract: Interpolated time-domain equivalent source method is extended to reconstruct the instantaneous surface normal velocity of a vibrating structure by using the time-evolving particle velocity as the input, which provides a non-contact way to overall understand the instantaneous vibration behavior of the structure. In this method, the time-evolving particle velocity in the near field is first modeled by a set of equivalent sources positioned inside the vibrating structure, and then the integrals of equivalent source strengths are solved by an iterative solving process and are further used to calculate the instantaneous surface normal velocity. An experiment of a semi-cylindrical steel plate impacted by a steel ball is investigated to examine the ability of the extended method, where the time-evolving normal particle velocity and pressure on the hologram surface measured by a Microflown pressure-velocity probe are used as the inputs of the extended method and the method based on pressure measurements, respectively, and the instantaneous surface normal velocity of the plate measured by a laser Doppler vibrometry is used as the reference for comparison. The experimental results demonstrate that the extended method is a powerful tool to visualize the instantaneous surface normal velocity of a vibrating structure in both time and space domains and can obtain more accurate results than that of the method based on pressure measurements.